REVITALISASI MODERASI BERAGAMA MELALUI PEMANFAATAN LITERASI DIGITAL OLEH GEN-Z - Jimmi Pindan Pute; Alferdi; Deflit Dujerslaim Lilo (Institut Agama Kristen Negeri Toraja, 2023)
Abstract : Religious moderation is the key to building equality, balance and tolerance between religions in Indonesia. Until now, the appreciation of the values of religious moderation has not shown the main purpose of the birth of a religion. This has resulted in the emergence of various conflicts, misunderstandings and disputes between one religious group and another. This situation should be re-evaluated especially with the hope of achieving a better future for Indonesia, especially in order to achieve Golden Indonesia in 2045. The purpose of this writing is to describe and describe the development of digital literacy by generation Z to achieve the revitalization of religious moderation, for the realization of Indonesia. gold in 2045. Digital literacy needs to be developed, because the thing that touches human life the most today is technology. The use of technology is expected to have a positive impact on its users because it is used as a literacy medium. The method used is descriptive qualitative with a literature study approach. The author will utilize sources such as books and journals, which are appropriate to the topics in this article. This research shows that revitalizing religious moderation can be implemented through digital literacy technology, by: forming interfaith network communities, disseminating information and constructive content between religious adherents, opening online discussions about religious tolerance and holding online competitions with the theme of religious moderation. Moderasi beragama adalah kunci membangun kesamarataan, keseimbangan dan toleransi antar agama di Indonesia. Sampai saat ini penghayatan terhadap nilai-nilai moderasi beragama belum menunjukan tujuan utama lahirnya suatu agama. Hal ini yang mengakibatkan munculnya berbagai konflik, kesalahpahaman dan pertikaian antar kelompok agama yang satu dengan agama yang lain. Situasi tersebut mestinya di evaluasi kembali terutama dengan harapan untuk mencapai masa depan Indonesia yang lebih baik, khususnya dalam rangka mencapai Indonesia Emas di tahun 2045. Tujuan penulisan ini adalah menguraikan serta mendeskripsikan pengembangan literasi digital oleh generasi Z untuk mencapai revitalisasi moderasi beragama, demi terwujudnya Indonesia emas tahun 2045. Literasi digital perlu untuk dikembangkan, karena hal yang paling banyak menyentuh kehidupan manusia saat ini adalah teknologi. Penggunaa teknologi diharapkan membawa dampak positif bagi penggunanya karena digunakan sebagai media literasi. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kepustakaan. Penulis akan memanfaatkan sumber-sumber seperti buku maupun jurnal, yang sesuai dengan topik dalam artikel ini. Penelitian ini menujukkan bahwa merevitalisasi moderasi agama dapat diterapkan melalui teknologi literasi digital, dengan cara: membentuk komunitas jaringan antar agama, menyebarkan informasi dan konten-konten yang bersifat membangun antar pemeluk agama, membuka diskusi-diskusi online tentang toleransi beragama dan mengadakan lomba-lomba online dengan tema moderasi beragama.